Developing Demangan Village’s Tourism Identity: A Support Program for the Menara Kudus Heritage Area - Via Amalia; Inaya Sari Melati; Rusdarti (Indonesian Journal of Devotion and Empowerment, 2025)
This community service program was carried out to support the development of locally based tourism in Demangan Village, which is strategically located near the Kudus Tower. The initiative focused on assisting the local community in shaping a tourism identity that reflects the village's unique culture and historical heritage. A total of 27 participants, including MSME representatives, community activists, and tourism managers, actively took part in the program. The community engagement process was conducted through an educational and participatory approach, including presentations, group discussions, and village potential mapping. To assess the program’s effectiveness, participants completed a pre-test before the activities began and a post-test afterward. The evaluation showed a significant improvement in participants’ understanding of tourism identity concepts, with an average score increase of 35%. Beyond improved comprehension, participants also expressed a strong commitment to developing a more authentic and compelling tourism narrative. The outcomes of this program are expected to serve as a foundation for sustainable initiatives aimed at positioning Demangan Village as a vital contributor to the cultural tourism image of Kudus. Ongoing mentorship and broader involvement of local stakeholders are identified as the next strategic steps toward realizing a competitive tourism village rooted in local identity.